Circular letter of Aceh’s Governor (ad interim) number 450/21770/2019: amid fanaticism and its controversy (content analysis) - Zulkarnain Zulkarnain (State Institute of Islamic Studies (IAIN) Salatiga, 2020)
The purpose of this research is to discuss the Circular Letter of Aceh’s Governor (ad interim) number: 450/21770/2019 concerning “the prohibition of holding recitation other than the i’tiqad Ahlu Sunnah wal Jama’ah which caused controvercy and turmoil of religious life in Aceh because it only allows one understanding of fiqih and prohibits others. This is a normative / doctrinal research using a content analysis approach. The results show that the Aceh Government regulations contained in Circular Letter Number: 450/21770/2019 have brought negative precedents for religious harmony in Aceh, especially the freedom to understand and carry out the understanding of Islam in various madhhab.